2021
DOI: 10.1021/acsami.1c03269
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Polyoxometalate Salt Adhesion by Butyltin Functionalization

Abstract: Polyoxometalate (POM)-based ionic liquids, with nearly infinite compositional variations to fine-tune antimicrobial and physical properties, function as water purification filters, anticorrosion/antibacterial coatings for natural stones, self-repairing acid-resistant coatings, catalysts, and electroactive, stable solvents. By combining hydrophobic quaternary ammonium cations (QACs; tetraheptylammonium and trihexyltetradecylammonium) with butyltin-substituted polyoxotungstates [(BuSn)3(α-SiW9O37)] via repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…When comparing the date of the first POMs studies described against viruses and cancer, respectively, at 1971 and 1965 [39,40], the antibacterial activities can be considered recent (1993). However, insights in POMs as anti-microbial agents or adjuvants, as well as POM-ILs as antibacterial coatings, have been attracting interest by offering mechanisms of action different from other recent antibacterial therapies [41][42][43][44][45][46][47][48][49][50]. On the other hand, many POMs have poor antibacterial activity, but possess excellent redox activity, and their use as biosensors for bacterial detection has been described [51].…”
Section: Antibacterial Activity Of Polyoxometalatesmentioning
confidence: 99%
“…When comparing the date of the first POMs studies described against viruses and cancer, respectively, at 1971 and 1965 [39,40], the antibacterial activities can be considered recent (1993). However, insights in POMs as anti-microbial agents or adjuvants, as well as POM-ILs as antibacterial coatings, have been attracting interest by offering mechanisms of action different from other recent antibacterial therapies [41][42][43][44][45][46][47][48][49][50]. On the other hand, many POMs have poor antibacterial activity, but possess excellent redox activity, and their use as biosensors for bacterial detection has been described [51].…”
Section: Antibacterial Activity Of Polyoxometalatesmentioning
confidence: 99%
“…Combining with hydrophobic quaternary ammonium cations and butyltin-substituted polyoxotungstates [(BuSn)3(α-SiW9O37)], Nyman et al obtained phase-pure hybrid POMs salts, which showed strong antibacterial activity against Escherichia coli [119] .…”
Section: Bacteriostatic Applicationmentioning
confidence: 99%